Surface and Interface Analysis - Holze, R. (Springer, 2017)
A broad, almost encyclopedic overview of spectroscopic and other analytical techniques useful for investigations of phase boundaries in electrochemistry is presented. The analysis of electrochemical interfaces and interphases on a microscopic, even molecular level, is of central importance for an improved understanding of the structure and dynamics of these phase boundaries. The gained knowledge will be needed for improvements of methods and applications reaching from electrocatalysis, electrochemical energy conversion, biocompatibility of metals, corrosion protection to galvanic surface treatment and finishing. The book provides an overview as complete as possible and enables the reader to choose methods most suitable for tackling his particular task. It is nevertheless compact and does not flood the reader with the details of review papers.